Lecturers’ Perception in Using YouTube for Teaching ESP - Fitria Nur Hamidah; Nostalgianti Citra Prystiantanta (Linguistic, English Education and Art (LEEA) Journal, 2023)
Information and communication technology (ICT) developments have completely changed how education is delivered. The lecturers especially English for Specific Purposes lecturers have been encouraged to use websites such as YouTube to promote better and best learning among the ‘Net Generation’ students. YouTube is an option media for teaching listening of ESP. The purposes of this study are to explain the benefits of YouTube in ESP classes especially in teaching listening based on the lecturers’ perception. This study used descriptive qualitative research design. YouTube is also one of websites that can support ESP teaching and Learning Process especially in listening. YouTube video is shared to the students by the lecturers when they teach listening of ESP in the class. Using YouTube in teaching listening of ESP classes was very benficial for the lecturers and the students. Besides, the lecturers’ perceptions on using YouTube were very interesting and useful teaching and learning in ESP classes. Keywords: YouTube, Teaching ESP, ESP classes.